Impact of Online Education on Student Emotional Well-being - Sazdovska-Pigulovska, Milena (Educational Role of Language Journal. Linguistic Well-being (Before, During, and After the Pandemic), 2021-2(6), Poland, 2021)
The shift to full online education has resulted in tremendous changes, such as creation of virtual classrooms, digital collaboration and distance learning. Students not only had to learn how to participate in virtual collaborative environments, but they are still adjusting to new methods of learning and using technology. Conducting online classes and exams at translation and interpreting studies is all the more challenging due to their interdisciplinary nature and a variety of generic and soft skills that suddenly need to be exercised online. Hence, after posing two research questions, it can be initially hypothesized that the digital transformation of education has an impact on students from an emotional point of view as well. Namely, it was visible that students dealt with the new arisen situation as well as with educational and social challenges in different ways and by expressing various emotional responses. This study aims to explore the ways in which tele-education affects student emotions and whether it influences their emotional well-being. For the purpose of this study, survey research was conducted among 91 students at undergraduate translation and interpreting studies in North Macedonia who were given the opportunity to explain how they personally dealt with educational novelties and challenges. The responses indicate whether students experience emotional consequences of (extended) online education. Based on the survey results, conclusions can be made about future practices that would benefit translation and interpreting students from an emotional point of view.
Keywords: online education, distance learning, emotional well-being, emotionally charged words, translation and interpreting studies